A Theoretical Study of Broadband Nearly Perfect Metasurface Absorber Based on Nanoarray of Titanium Nitride. Issue 7 (10th May 2019) - Piao, Rui‐Qi; Xu, Qing; Wong, Wing‐Han; Pun, Edwin Yue‐Bun; Zhang, De‐Long
Abstract: A metasurface perfect absorber working in whole visible regime is proposed on the basis of a sandwiched three‐layer structure formed by titanium nitride (TiN) nanoarray, antireflective MgF2 dielectric film, and TiN bottom layer. Each structural unit of the TiN array consists of a nanodisk and four symmetrically wrapped nanotriangles. The triangles play a role in increasing the absorption in the long wavelength region. The performance of the absorber was simulated as a function of its geometric parameters and the angle of incident beam as well. The results are discussed in terms of localized surface plasmonic resonance mechanism and dispersion effect of TiN, and the absorption features are qualitatively explained on the basis of electric field and power flow distributions. Optimal geometric parameters are presented. With the optimal parameters, the absorber would realize an averaged absorption of 98.3% over the entire visible region from 350 to 800 nm, with a peaking absorption 99.9% at 720 nm and a band of 482–780 nm having an absorption >99%. In addition, the absorber also shows polarization insensitivity and good angular acceptance capability of incident beam. The unique and compact structure has great potential application in fields of (thermo‐)photovoltaics, light trapping, and cloaking. Abstract : A broadband metasurface absorber with a sandwiched three‐layer structure of TiN bottom film, anti‐reflective MgF2 dielectric film and symmetric TiN nano‐array is proposed and simulated. Optimal geometric parameters are presented. The resultant absorber would display nearly perfect broadband absorption over the entire visible region, suggesting great application potential in fields of (thermo‐) photovoltaics, light trapping and cloaking.